Resilience of urban value chains during the COVID-19 pandemic: Evidence from dairy and vegetable chains in Ethiopia - Hirvonen, Kalle; Mohammed, Belay; Habte, Yetimwork; Tamru, Seneshaw; Abate, Gashaw T.; Minten, Bart (International Food Policy Research Institute, 2022)
At the beginning of the COVID-19 pandemic, many researchers and international organizations voiced concerns about the resilience of food value chains amid lockdowns and border closures, particularly in low- and middle-income countries (Laborde et al. 2020; Reardon, Bellemare, and Zilberman 2020; Resnick 2020). This chapter explores the pandemic’s effects on dairy and vegetable value chains in Ethiopia’s capital through mid-2021. Despite early fears about the pandemic’s impacts, survey data show that these urban value chains quickly rebounded after an initial period of fragility, demonstrating resilience over the research period. Amid tremendous uncertainty and market volatility, most value chain actors also indicated that the pandemic had not negatively affected their business activities.